Emocional branding aplication in the funeral sector marketing - Álvarez - Pérez, Danna Paola; Pacheco - Sánchez , Carlos Alberto (Universidad Francisco de Paula Santander, 2018)
Emotional branding awakens in the client the desire to believe and remain in a company because of the capacity to inspire, motivate and enjoy one or more products or services. However, what has been described is difficult to execute in the funeral sector of Ocaña given the economic activity that they carry out, which is why there is the possibility that these companies omit or do not design assertive branding strategies. Consequently, the aim was to find out about marketing actions through emotional branding in companies providing funeral services. For this purpose, a quantitative research was required in the funeral sector with a non-probabilistic sample, where the survey was applied to 5 entities belonging to the sector. As a result, it is deduced that in the funeral sector only 20% have knowledge about the term, but it is not achieved a correct applicability in the marketing processes.